Visual short-term memory binding deficit in familial Alzheimer's disease. (May 2016) - Liang, Yuying; Pertzov, Yoni; Nicholas, Jennifer M.; Henley, Susie M.D.; Crutch, Sebastian; Woodward, Felix; Leung, Kelvin; Fox, Nick C.; Husain, Masud
Abstract: Long-term episodic memory deficits in Alzheimer's disease (AD) are well characterised but, until recently, short-term memory (STM) function has attracted far less attention. We employed a recently-developed, delayed reproduction task which requires participants to reproduce precisely the remembered location of items they had seen only seconds previously. This paradigm provides not only a continuous measure of localization error in memory, but also an index of relational binding by determining the frequency with which an object is misplaced to the location of one of the other items held in memory. Such binding errors in STM have previously been found on this task to be sensitive to medial temporal lobe (MTL) damage in focal lesion cases. Twenty individuals with pathological mutations in presenilin 1 or amyloid precursor protein genes for familial Alzheimer's disease (FAD) were tested together with 62 healthy controls. Participants were assessed using the delayed reproduction memory task, a standard neuropsychological battery and structural MRI. Overall, FAD mutation carriers were worse than controls for object identity as well as in gross localization memory performance. Moreover, they showed greater misbinding of object identity and location than healthy controls. Thus they would often mislocalize a correctly-identified item to the location of one of the other items held in memory. Significantly, asymptomatic gene carriers – who performed similarly to healthy controls on standard neuropsychological tests – had a specific impairment in object-location binding, despite intact memory for object identity and location. Consistent with the hypothesis that the hippocampus is critically involved in relational binding regardless of memory duration, decreased hippocampal volume across FAD participants was significantly associated with deficits in object-location binding but not with recall precision for object identity or localization. Object-location binding may therefore provide a sensitive cognitive biomarker for MTL dysfunction in a range of diseases including AD.